2009
DOI: 10.1002/adsc.200800528
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Alkyl Halides by Triethylsilane Based on a Cationic Iridium Bis(phosphinite) Pincer Catalyst: Scope, Selectivity and Mechanism

Abstract: A highly efficient procedure for the reduction of a broad range of alkyl halides by triethylsilane based on a cationic iridium bis(phosphinite) pincer catalyst has been discovered and developed. This reduction chemistry is chemoselective and has unique selectivities compared with conventional radical-based processes and the aluminum trichloride/ triethylsilane (AlCl 3 /Et 3 SiH) and triphenylmethyl tetrakis [pentafluorophenyl]borate/triethylsilane {[Ph 3 C] [BA C H T U N G T R E N N U N G (C 6 F 5 ) 4 ]/Et 3 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…Other examples of ionic mechanisms involving hydrosilanes include substrates such as carbonyl [8] and ether [9] compounds (C-O and C=O bonds), halogenated compounds [10] (Chalide bonds) and N-heterocycles [11] (C=N bonds). In these cases the splitting of the Si-H bond takes places by interaction of a metal center with the hydrogen atom, and the substrate with the silicon atom.…”
mentioning
confidence: 99%
“…Other examples of ionic mechanisms involving hydrosilanes include substrates such as carbonyl [8] and ether [9] compounds (C-O and C=O bonds), halogenated compounds [10] (Chalide bonds) and N-heterocycles [11] (C=N bonds). In these cases the splitting of the Si-H bond takes places by interaction of a metal center with the hydrogen atom, and the substrate with the silicon atom.…”
mentioning
confidence: 99%
“…Thus far, investigations into the reduction of halides and sulfonates using Pd, [15] Ni, [16] and Ir [17] have mostly been focused on unfunctionalized substrates. Thus far, investigations into the reduction of halides and sulfonates using Pd, [15] Ni, [16] and Ir [17] have mostly been focused on unfunctionalized substrates.…”
mentioning
confidence: 99%
“…[23] The reaction is compatible with aryl chlorides, bromides, and iodides, all of which are typically reactive in both transition-metal-catalyzed and free-radical reductions (14)(15)(16)(17). We found that, with slight modifications to existing methods, primary triflates can be efficiently prepared with minimal purification.…”
mentioning
confidence: 99%
See 2 more Smart Citations